Anisotropy of track revelation in epidote: Results of a step etching experiment with Kr-86 ion tracks - Curvo, E. A. C. [UNESP]; Guedes, S.; Alencar, I.; Nakasuga, W. M. [UNESP]; Tello S, C. A. [UNESP]; Iunes, P. J.; Hadler, J. C. (Pergamon-Elsevier B.V. Ltd, 2011)
Epidote etching anisotropy has been studied through step etching of Kr-86 (300 MeV) ion tracks. A slice of epidote natural monocrystal was taken from the (010) plane and then divided into five pieces. Each piece was then irradiated with ions whose incidence angles (zenith angles) were of 15 degrees, 30 degrees, 45 degrees, 60 degrees and 75 degrees with respect to y-axis. The azimuthal angle of incidence of the ions was the same for the pieces 15 degrees, 60 degrees, 75 degrees and 180 degrees apart for the pieces 30 degrees and 45 degrees. Etching times were of 10, 20, 30, 40 and 50 min (HF 40%, 35 degrees C). The results show that etching velocities of ion tracks are higher in directions closer to the y-axis. The mean lengths of the ion tracks, regarding the angles, were of 23.14 +/- 0.21 (15 degrees); 19.89 +/- 0.08 (30 degrees); 19.39 +/- 0.04 (45 degrees) and 16.59 +/- 0.10 mu m (60 degrees). Since no tracks were identified in the 75 degrees aliquot it was assumed that the epidote has a critical angle, for recording of ion tracks with this mass/energy ratio, between 60 degrees and 75 degrees. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Epidote; Anisotropy; Step etching; Ion tracks